If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = -6x + -3(5 + -3x) 6x = -6x + (5 * -3 + -3x * -3) 6x = -6x + (-15 + 9x) Reorder the terms: 6x = -15 + -6x + 9x Combine like terms: -6x + 9x = 3x 6x = -15 + 3x Solving 6x = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6x + -3x = -15 + 3x + -3x Combine like terms: 6x + -3x = 3x 3x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 3x = -15 + 0 3x = -15 Divide each side by '3'. x = -5 Simplifying x = -5
| (4x-12)(7x+6)=0 | | (4x-12)(7x+6)=0 | | 3x+1x+1x=900000 | | 27x^2+12=36x | | 67=N-84 | | N+6=15 | | 3(d+2e)-11d= | | k-(-8k)= | | 3*(2x-4)=24 | | 48-3x=15x+22 | | 2d-5-3d-8= | | -3p+5p= | | -32-3w-5w=0 | | 8t+t= | | 2*(2x-4)=24 | | 6x+2y=22 | | 2*(2x+3)=3*(x+10) | | 8a+2=6-10a | | -6x+4=1 | | 4x^2+3xy-2x^2+4x^2= | | 10-10x=37-31x | | -8-4x=6x+19 | | 58-3x=6x+18 | | 90-30x=2x+15 | | 6x-37=5 | | -7+5x=53 | | 60-5x=4x+19 | | 20+8x=44 | | 14x+18=5x+252 | | 5y-3=7-4y | | 4x+29=12x-59 | | 3x+5(22-x)=80 |